Optimization of Antitumor Modulators of Pre-mRNA Splicing - Lagisetti, Chandraiah; Palacios, Gustavo; Goronga, Tinopiwa; Freeman, Burgess; Caufield, William; Webb, Thomas R (Journal of medicinal chemistry, 2013)
The spliceosome regulates pre-mRNA splicing, which is a critical process in normal mammalian cells. Recently, recurrent mutations in numerous spliceosomal proteins have been associated with a number of cancers. Previously, natural product antitumor agents have been shown to interact with one of the proteins that is subject to recurrent mutations (SF3B1). We report the optimization of a class of tumor-selective spliceosome modulators that demonstrate significant in vivo antitumor activity. This optimization culminated in the discovery of sudemycin D6, which shows potent cytotoxic activity in the melanoma line SK-MEL-2 (IC50 = 39 nM) and other tumor cell lines, including JeKo-1 (IC50 = 22 nM), HeLa (IC50 = 50 nM), and SK-N-AS (IC50 = 81 nM). We also report improved processes for the synthesis of these compounds. Our work supports the idea that sudemycin D6 is worthy of further investigation as a novel preclinical anticancer agent with application in the treatment of numerous human cancers.